Tatalaksana Perawatan Doskolorasi Intrinsik Dengan Perawatan Saluran Akar Dan Metode Walking Bleach - Ie Elline Istanto (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Intrinsic discoloration of the tooth can be caused following trauma, loss of vitality, endodontic treatment, and restorative procedures apart from known local and systemic factors. Tooth bleaching, veneering or placement of a full coverage crown are treatment options for discolored tooth. Non-vital teeth that are extensively discolored are highly receptive for bleaching techniques. This case report discusses a patient having discoloration in the anterior region with caries in proximal distal. In  clinical  aspects  considerations,  it was essential for  a minimally  invasive and achieve esthetic treatment. Objective: This case report is written to bring forward the proper and successful management in esthetic treatment of anterior maxilla in discoloration with caries in proximal case. Case and management : A 20 years old female patient complained of discoloration in 11 and feels uncomfortable with her condition. On examination, 11 caries D6 ICDAS, Mount & Hume site 2 size 3 and Class IV G.V Black. In first appointment, patient was informed about the treatment and signed informed consent. Endodontics treatment was performed in multiple visit. Root canal preparation was performed using TF Adaptive   25/.08, 35/.06, 50/.04. Obturation used warm vertical compaction. After finishing the endodontics treatments 2 mm  wing barrier was built to prepare the walking bleach method. Walking bleach using hydrogen peroxide 35% was applicated in pulp chamber for 1 week.  In next visit, composite restoration was done. Conclusion: Management in intrinsic discoloration  can be done by performing endodontic treatment , walking bleach combined with composite restoration  and they can give satisfactory result.